The Impact of Social Capital and Organizational Culture on Improving Organizational Performance - Nuryanto, Uli Wildan; Djamil Mz, Masyhudzulhak; Sutawidjaya, Ahmad Hidayat; Saluy, Ahmad Badawi (International Review of Management and Marketing, 2020)
To run their business, many companies uses various types of capital, financial, technological, as well as natural and human resource–based. In fact, optimal use of these kinds of capital do not guarantee that company will get maximum performance. There is still one important type of capital, namely social capital, which is an asset and instrument characterizing the interaction between employees and management. Social capital can also be conceptualized as a company's organizational culture. Here, interviews were conducted with the management of a chemical manufacturer see how synergizing between corporate strategy and support forms the organizational culture. This research focussed to the industrial chemical manufacture at Banten Province, Indonesia, which is the province with the third-largest number of chemical firms in Indonesia. This research using SEM-PLS method to measure 97 respondents from the managerial level. The final results provide a positive and significant relationship between social capital and organizational culture through competitive advantage and organizatioan performance. Competitive advantage also increased the relationship between social capital and organizational culture through the organizational performance. This result has implication for managerial levels to increase human resources performance so it can improve the firm's competitive advantage. Keywords: Social Capital, Organizational Culture, Competitive Advantage, Organizational Performance, Chemical manufacturer sector JEL Classifications: L2, M14 DOI: https://doi.org/10.32479/irmm.9923